1954
DOI: 10.1039/jr9540002243
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic azo-compounds. Part VI. The action of light on azoxy-compounds

Abstract: A number of azoxy-derivatives have been isomerised to o-hydroxyazoderivatives by exposure to sunlight, the oxygen atom migrating from nitrogen to the further nucleus. An intramolecular mechanism is therefore proposed.The supposed red " isomers " of the azoxynaphthalenes are mixtures. CUMMING and STEEL (J., 1923, 123, 2464) reported that exposure of yellow 1 : 1'-azoxynaphthalene to sunlight or ultra-violet light rapidly converted it into a red form. A similar change was claimed for 2 : 2'-azoxynaphthalene (Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…2,2'-Azoxytoluene is known to be unusual in that it gives photo products additional to those predicted by [ I ] (3), and similar anoinalous behaviour has also been observed recentiy for other o-substituted azoxybenrenes (4). The extra products are suppressed when 2,2'-azoxytoluene is photolyzed in the presence of 2-naphthol, and it has been suggested ( 5 ) that some intermediate such as 2, originally proposed by Badger and Buttery (6), has the ability to fragment into a diazonium ion. This may couple with 2-naphthol, giving l-otolylazo-2-naphthol 3 as an observed product.…”
mentioning
confidence: 77%
“…2,2'-Azoxytoluene is known to be unusual in that it gives photo products additional to those predicted by [ I ] (3), and similar anoinalous behaviour has also been observed recentiy for other o-substituted azoxybenrenes (4). The extra products are suppressed when 2,2'-azoxytoluene is photolyzed in the presence of 2-naphthol, and it has been suggested ( 5 ) that some intermediate such as 2, originally proposed by Badger and Buttery (6), has the ability to fragment into a diazonium ion. This may couple with 2-naphthol, giving l-otolylazo-2-naphthol 3 as an observed product.…”
mentioning
confidence: 77%
“…In the case of the dinaphthyl azoxy compounds containing the 1-and/or 2-naphthyl ring systems, rearrangement occurs preferentially to the 4-position of the 1-naphthyl ring if such is available. If such a position is not available, as in the case of 14, then ortho rearrangement to the 1-position of the 2-naphthyl ring system results, yielding the same product as obtained in the photochemically induced rearrangement (15).…”
Section: Discussionmentioning
confidence: 90%
“…The choice was made for convenience in preparation and also to avoid the raising of any question of ambiguity in our measurements from the possibility of isomerization of the azoxy group via an oxadiaziridine (16), prior to the photo-Wallach rearrangement. Such a possibility would appear to be ruled out by studies of orientation in the photo-Wallach rearrangement (10,17), but isomerization of 4'-into 4-methoxyazoxybenzene has been reported, implicating the participation of an oxadiaziridine intermediate (17,18), while the possible formation of diphenyloxadiaziridine as an initial side reaction in the photorearrangement of 4 has been proposed (19). Furthermore, Oae and co-workers found that a small amount of scrambling did, in fact, occur in the photo-rearrangement of [l-14C]4.…”
Section: Introductionmentioning
confidence: 99%
“…In order to specify particular extents of conversion, the disappearance of azoxy compound and the formation of product were first monitored spectroscopically with irradiations of unlabeled substrate. The formation of 2-hydroxyazobenzene (6) was monitored at 410nn-1, while the formation of 1-hydroxy-2,2'-azonaphthalene (10) was monitored at 505 nm. Solvents for photo-rearrangement were 95% ethanol for 4 and 1,2-dimethoxyethane (DME) for 8.…”
Section: Photo-rearrangementsmentioning
confidence: 99%